THE EFFECT OF STRATEGIC LEADERSHIP BEHAVIOR ON WORK PERFORMANCE THROUGH MEDIATOR VARIABLES OF ORGANIZATIONAL COMMITMENT AND JOB SATISFACTION WITH AN EMPHASIS ON MODERATING ROLE OF ORGANIZATIONAL CULTURE (CASE STUDY: PUBLIC AND PRIVATE BANKS IN GUILAN PROV - Shirzad Jahandoost, Mohammad Taleghani, Hamidreza Alipour (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The main purpose of this study is measuring the effect of strategic leadership behaviors on job performance through mediating variables of organizational commitment and job satisfaction with emphasis on the role of organizational culture. The research method is applicable in terms of purpose and in terms of descriptive-survey method. For the validity of the questionnaires in relation to its application in the tests from the point of view of technical professors as well as confirmatory factor analysis for the validity of the structure has been used and for its reliability Cronbach’s alpha method and combined reliability have been used. The population of this study includes all managers and employees of public and private banks in guilan province. In this research, the questionnaire was randomly distributed among managers and employees of public and private banks in gilan province. To test hypotheses, software SPSS16 and Smart PLS2 were used. The results show that inspirational motivation of the part of strategic leadership behaviors affects organizational commitment and job satisfaction, idealized influence of strategic leadership behaviors affects organizational commitment and job satisfaction. Flexibility-oriented culture and control-oriented culture have moderating effect on inspirational motivation with organizational commitment and job satisfaction. Flexibility-oriented culture and control-oriented culture have a moderating effect on organizational commitment and job satisfaction. Also organizational commitment and job satisfaction affect work performance.